Multicentre evaluation of music perception in adult users of Advanced Bionics cochlear implants. (January 2014) - Adams, Doris; Ajimsha, Khalid Mohamed; Barberá, Manuel Tomás; Gazibegovic, Dzemal; Gisbert, Javier; Gómez, Justo; Raveh, Eyal; Rocca, Christine; Romanet, Philipe; Seebens, Yvonne; Zarowski, Andrzej
Abstract : Objectives: To document musical listening and enjoyment in recipients of Advanced Bionics cochlear implants (CIs) and to compare musical perception in those using early coding strategies with subjects using the newer HiRes and HiRes 120 strategies. Methods: A questionnaire was completed by 136 adult subjects, including questions on the ability to identify specific musical features. The subjects were in three groups: those using early coding strategies ( n  = 29), HiRes ( n  = 59), and HiRes 120 ( n  = 48), and results were compared with a group of 84 normally hearing (NH) subjects. Results: Of the CI users, 79% reported listening to music. The NH group rated listening frequency and enjoyment higher than the CI users. Thirty-five users reported that they sang and this group had significantly higher overall performance. There were no significant differences in overall perception of specific musical features among the strategy groups, though some individual questions showed significantly higher performance in the HiRes 120 users. Discussion: Users of current CI technology show a high level of musical appreciation, though still significantly less than NH subjects. Frequency of listening and enjoyment were significantly correlated and active participation in musical activities, specifically singing, resulted in significantly higher overall performance scores.